(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Educational institutions play a major role in shaping individuals’ awareness of social and economic variables, modifying their attitudes towards them, and arousing their interest in them, especially those variables related to economic well-being, such as entrepreneurship. Graduate students constitute one of the most educated and innovative groups in society, and therefore their role in the field of entrepreneurship is of great importance. Universities are a good intellectual environment for creativity and entrepreneurial thinking to grow. However, there are potential challenges and obstacles that graduate students may face in achieving their entrepreneurial ambitions. The researcher relied on the questionnaire as a tool for collecting data, by conducting personal interviews with a number of members of the research sample. The questionnaire was distributed to 90 people, 80 were retrieved, and 5 were excluded because they were not suitable for analysis. Thus, the sample size reached 75 people from graduate students at Tishreen University. The researcher found that there are several obstacles to entrepreneurship from the point of view of graduate students at Tishreen University, the most prominent of which were financial obstacles, then academic obstacles, then social obstacles. The researcher recommended the necessity of working to overcome all obstacles in entrepreneurship by developing a culture of entrepreneurship among graduate students, starting with academic curricula, linking theoretical study to practical and field study, providing financial support to graduate students, and spreading a culture in society about the importance of entrepreneurship and its role in development. Economic and social.